2019
DOI: 10.3390/pharmaceutics11070314
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bioinspired Gelatin and Gelatin/Chitosan Bilayer Hydrofilms for Wound Healing

Abstract: In the current study, we developed a novel gelatin-based bilayer wound dressing. We used different crosslinking agents to confer unique properties to each layer, obtaining a bioinspired multifunctional hydrofilm suitable for wound healing. First, we produced a resistant and non-degradable upper layer by lactose-mediated crosslinking of gelatin, which provided mechanical support and protection to overall design. For the lower layer, we crosslinked gelatin with citric acid, resulting in a porous matrix with a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…These values appeared to be outside the range recommended for an ideal dressing. However, the WVTR values obtained herein are within the range displayed by commercial wound dressings (426-2047 g/m 2 /day) [61].…”
Section: Water Vapor Transmission Rate (Wvtr) Analysissupporting
confidence: 67%
“…These values appeared to be outside the range recommended for an ideal dressing. However, the WVTR values obtained herein are within the range displayed by commercial wound dressings (426-2047 g/m 2 /day) [61].…”
Section: Water Vapor Transmission Rate (Wvtr) Analysissupporting
confidence: 67%
“…The obtained RosA-gelatin edible film possessed excellent ultraviolet barrier capacity and exhibited good antioxidant properties and long-term antibacterial activity, with promising applications in the fields of food and pharmaceutical packaging. Garcia-Orue et al developed an elegant gelatin-based bilayer suitable for wound healing [63]. They first prepared a lactose-based gelatin, for mechanical support and protection, and then cross-linked a lower layer of citric acid and chitosan for antioxidant and swelling properties.…”
Section: Polymeric Formulationsmentioning
confidence: 99%
“…In vitro experiments for each type of scaffold revealed that cell viability at 3 days was at least 90% for those including chitosan. In vivo experimentation was carried out in mice, rats, and ex vivo human skin explants, and resulted in some scaffolds performing better than the control groups, such as the curcumin-loaded gel [106] and catechol-loaded terpolymer [107], while the gelatin-crosslinked [108] scaffold performed more poorly than the controls. These results indicate that while chitosan-mixed scaffolds may function well in an in vitro environment, further experimentation must be conducted on their use in in vivo situations.…”
Section: Antibacterial Scaffoldsmentioning
confidence: 99%